Tabligh Akbar on the Manganan Tradition in Tuban: The Dynamics of Local Religion and Culture from a Syncretism Perspective - Muhammad Nouval Maulana Dirna; Mahmud Muhsinin; Muhammad Wahid Nur Tualeka (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2025)
The Manganan tradition in Tuban is a cultural practice passed down through generations, undergoing transformations due to the influence of Islamization. Initially, this tradition served as an expression of gratitude to ancestors for agricultural harvests. However, with the introduction of Islamic teachings, a transformation occurred, strengthening Islamic values within the practice. One of the most significant changes is the integration of Tabligh Akbar into the Manganan ceremony. This study employs a qualitative approach with phenomenological methods to understand the religious and cultural dynamics from a syncretic perspective. The findings reveal that Tabligh Akbar plays a role in Islamizing the Manganan ritual without entirely eliminating local cultural elements. This process reflects a pattern of syncretism, where the community maintains traditional values while adapting religious teachings. Despite shifts in ritual practices, this tradition remains upheld as a form of solidarity, mutual cooperation, and respect for religious values. Thus, the Manganan tradition combined with Tabligh Akbar serves as an example of how religion and culture can interact harmoniously in a dynamic unity.The Manganan tradition in Tuban is a cultural practice passed down through generations, undergoing transformations due to the influence of Islamization. Initially, this tradition served as an expression of gratitude to ancestors for agricultural harvests. However, with the introduction of Islamic teachings, a transformation occurred, strengthening Islamic values within the practice. One of the most significant changes is the integration of Tabligh Akbar into the Manganan ceremony. This study employs a qualitative approach with phenomenological methods to understand the religious and cultural dynamics from a syncretic perspective. The findings reveal that Tabligh Akbar plays a role in Islamizing the Manganan ritual without entirely eliminating local cultural elements. This process reflects a pattern of syncretism, where the community maintains traditional values while adapting religious teachings. Despite shifts in ritual practices, this tradition remains upheld as a form of solidarity, mutual cooperation, and respect for religious values. Thus, the Manganan tradition combined with Tabligh Akbar serves as an example of how religion and culture can interact harmoniously in a dynamic unity.